Impact Loading and Modelling a Multilayer Aluminium Corrugated/Fin Core: the Effect of the Insertion of Imperfect Fin Layers - Sarıkaya, Mustafa; Güden, Mustafa; Taşdemirci, Alper; Taşdemirci, Alper; Güden, Mustafa (John Wiley and Sons Inc., 2019)
The quasi-static compression (0.0048 m/s) and Taylor-like impact (135, 150, and 200 m/s) loading of a multilayer 1050 H14 aluminium corrugated core were investigated both experimentally and numerically in LS-DYNA using the perfect and imperfect sample models. In the imperfect sample models, one or two layers of corrugated fin structure were replaced by the fin layers made of bent-type cell walls. The localised deformation in the quasi-static imperfect models of cylindrical sample started at the imperfect layers, the same as the tests, and the layers were compressed until about the densification strain in a step-wise fashion. The localised deformation in the perfect models, however, started at the layers at and near the top and bottom of the test sample. In the shock mode, the sample crushed sequentially starting at the impact end layer regardless the perfect or imperfect sample models were used. Furthermore, the perfect and imperfect models resulted in nearly the same initial crushing stresses in the shock mode. The layer strain histories revealed a velocity-dependent layer densification strain. Both model types, the imperfect and perfect, well approximated the stress-time histories and layer deformations of the shock mode. The rigid perfectly plastic locking model based on the numerically determined densification strains also showed well agreements with the experimental and numerical plateau stresses of the shock mode.
Keywords: Cellular structure; Impact loading; Imperfection; Modelling; Shock stress